Corruption in Infrastructure Projects: Case Studies and Juridical Analysis - Noviya, Anis; Samsidar, Samsidar; Romdoni, Muhamad (PT. Anagata Sembagi Education, 2025)
The infrastructure sector in Indonesia is one of the most vulnerable arenas to corruption because of its capital-intensive, complex, and multi-year characteristics. Projects such as the construction of toll roads, bridges, and other public facilities are often abused through budget mark-ups, fictitious procurement, and collusion in auctions. This study aims to analyze the application of Article 2 and Article 3 of Law Number 20 of 2001 in tackling corruption in infrastructure projects. Using a normative juridical approach and case studies, this study highlights that corruption in infrastructure projects is systemic, involves many actors, and is difficult to dismantle due to weaknesses in the procurement, oversight, and legal proofing systems. The results of the study show that the effectiveness of these articles is greatly influenced by the context of implementation in the field, including the understanding of law enforcement officials of the project corruption modus operandi. In addition, weak surveillance systems, low transparency, and technical and political obstacles exacerbate the situation. Therefore, legal reform is not enough if it is not accompanied by institutional reform and digitalization of accountable procurement. In conclusion, the eradication of infrastructure corruption must be carried out through a comprehensive, interdisciplinary, and adaptive legal approach to the complexity of project governance in the public sector.